KNOWLEDGE AND COMPLIANCE TO PRACTICE OF PREVENTIVE MEASURES TO COVID-19 AMONG NURSES IN A SELECTED TERTIARY HOSPITAL IN SOUTH-SOUTH, NIGERIA: covid-19 Preventive measures among nurses - Linda C, Odikpo; Calistus, Ezike Okwudilli; Evert O, Onyia; Chiedu, Egbuniwe Michel; Ilo, Clementina I.; Helen, Obidife I.; Nwankwo, Clementina U. (African Journal of Infectious Diseases (AJID), 2022)
Background: Healthcare providers have been at the frontline of the response to the COVID-19 disease. Many of them have contracted the disease, and some of them already dead. This study assessed the knowledge, compliance with preventive measures and determined the relationship between knowledge and practice of preventive strategies to COVID-19 among nurses working in a selected hospital in South-South Nigeria. Materials and methods: A cross-sectional descriptive design guided the study. Census method guided the recruitment of all the 378 nurses in the hospital who met the study's inclusion criteria. Results: Majority (360 [95.2%]) of the nurses had good knowledge of the preventive measures to COVID-19 and 311 (82.4%) of the nurses adhere strictly to practice of the preventive strategies to COVID-19. Educational level and years of experience are determinants of knowledge about preventive measures to COVID-19 (p<0.05 respectively) while knowledge, sex, level of education, years of experience, and unit of practice are determinants of compliance to preventive measures to COVID-19 among the nurses (p<0.001). Female nurses (p=0.012), RN/RM qualified nurses (p=0.037), nurses with more than five years of experience, and those in children ward (p=0.020) and maternity complex (p=0.003) significantly comply more to the preventive measures for COVID-19 as shown by their adjusted odds ratios. Conclusion: As knowledge to COVID-19 preventive strategies continues to increase among health workers, there is a need to translate this knowledge into adequate practice in order to minimise the hazardous effect of the pandemic on the health workers especially nurses.